Mulheres mutiladas e mulheres desonradas:a importância da luta de Mukhtar Mai e Khady Koita aos direitos humanos das mulheres. - VILARINHO, Murilo Chaves (2011)
This dissertation is an analysis from the reports of two women who broke with the patriarchal tradition of their societies and resolved to fight for the dignity of women. We speak of Mukhtar Mai in Pakistan and Senegal Khady Koita. The first victim of gang rape was ordered by the tribal council of Meerwala in Pakistan. And the second had her clitoris removed at 7 years old in a traditional ritual purification procedure in Senegal. So, each in its context, both women have rebelled against the acts suffered and denounced the violence is committed in the name of tradition, or honor the man. Denouncing the violence were the world, a feat that became a symbol for the human rights of women. Mukhtar Mai and Khady gained fame locally and internationally in the fight for an end to honor killings and female genital mutilation. It's about attitudes to break with tradition, and the fight passed the reflections of this work. That is, in light of feminist theories, the field of Human Rights (formed by means of treaties, conventions and humanitarian letters), and human rights of women who seek to understand the break with the patterns of subordination in patriarchal societies entrenched like remember Therborn (2006), and they represent the achievements of these individuals for Human Rights in general and the condition of women in particular.